Application of a Novel Brain Arteriovenous Malformation Endovascular Grading Scale for Transarterial Embolization - Bell, D.L. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: The advent of modern neuroendovascular techniques has highlighted the need for a simple, effective, and reliable brain arteriovenous malformation endovascular grading scale. A novel scale of this type has recently been described. It incorporates the number of feeding arteries, eloquence, and the presence of an arteriovenous fistula component. Our aim is to assess the validity of this grading scale. MATERIALS AND METHODS: We retrospectively reviewed all suspected brain arteriovenous malformations at Massachusetts General Hospital from 2005 to 2013, identifying 126 patients who met the inclusion criteria. Spearman correlations between endovascular and Spetzler-Martin grading scales and long-term outcomes were performed. Median endovascular grades were compared between treatment modalities and endovascular outcomes. Binary regression analysis was performed with major endovascular complications as a dichotomized dependent variable. Intraclass correlation coefficients were calculated for interobserver reliability of the endovascular grading scale. RESULTS: A significant Spearman correlation between the endovascular grade and the Spetzler-Martin grade was demonstrated (ρ = 0.5, P < .01). Differences in the median endovascular grades between the endovascular cure (median = 2) and endovascular complication groups (median = 4) (P < .05) and between the endovascular cure and successful multimodal treatment groups (median = 3) (P < .05) were demonstrated. The endovascular grade was the only independent predictor of complications (OR = 0.5, P < .01). The intraclass correlation coefficient of the endovascular grade was 0.71 (P < .01). CONCLUSIONS: Validation of a brain arteriovenous malformation endovascular grading scale demonstrated that endovascular grades of ≤II were associated with endovascular cure, while endovascular grades of ≤III were associated with multimodal cure or significant lesion reduction and favorable outcome. The endovascular grade provides useful information to refine risk stratification for endovascular and multimodal treatment.